2011
DOI: 10.5811/westjem.2011.11.6820
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Emergency Department Preference for Access to Healthcare

Abstract: Introduction:African-Americans are more likely than Caucasians to access healthcare through the emergency department (ED); however, the reasons behind this pattern are unclear. The objective is to investigate the effect of race, insurance, socioeconomic status, and perceived health on the preference for ED use.Methods:This is a prospective study at a tertiary care ED from June to July 2009. Patients were surveyed to capture demographics, healthcare utilization, and baseline health status. The primary outcome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 22 publications
(27 reference statements)
2
41
0
Order By: Relevance
“…Studies have identified poor social support and communication with providers, limitation of financial and transportation resources, reliance on opioids, and lack of belief in and inadequacy of pain control as barriers to multimodality pain management . For these reasons and because of findings showing that regardless of access to care, some patients continue to preferentially utilize the ED for ambulatory care–sensitive conditions (such as chronic pain ), ED‐based interventions for chronic pain management (such as case management, use of chronic pain protocols, and pain specialist consultation in the ED) should be developed to complement outpatient services. Some studies have explored the use of individualized home pain management programs and community health workers who provide social support, navigation of health systems and resources, and counseling, for the management of chronic pain in sickle cell disease .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified poor social support and communication with providers, limitation of financial and transportation resources, reliance on opioids, and lack of belief in and inadequacy of pain control as barriers to multimodality pain management . For these reasons and because of findings showing that regardless of access to care, some patients continue to preferentially utilize the ED for ambulatory care–sensitive conditions (such as chronic pain ), ED‐based interventions for chronic pain management (such as case management, use of chronic pain protocols, and pain specialist consultation in the ED) should be developed to complement outpatient services. Some studies have explored the use of individualized home pain management programs and community health workers who provide social support, navigation of health systems and resources, and counseling, for the management of chronic pain in sickle cell disease .…”
Section: Discussionmentioning
confidence: 99%
“…Subjects who experienced high congestion (greater than nine people in the waiting room, the fiftieth percentile) or those who were recruited from farther away locations (longer than 18 minutes by car, the fiftieth percentile) also elected to receive more services when randomized to a black doctor than a non-black doctor. 14 African Americans visit the emergency room more often than non-Hispanic whites, which some have linked to lack of insurance, lower socioeconomic status, and mistrust that precludes health care utilization until an advanced stage of illness (Arnett et al 2016, Brown et al 2012. Panel C demonstrates that those who use the emergency room more often increased their demand for services when randomized to a black doctor.…”
Section: A Communication Between Patients and Doctorsmentioning
confidence: 98%
“…For example, in comparison to European American patients, African American patients see themselves as being in worse health and receiving lower quality of care (Smedley et al, 2003). They are more likely to visit the emergency department and they have fewer physician visits per year (Brown et al, 2012; Smedley et al, 2003). In the clinician’s office, for example, physicians are more verbally dominant and engage in less patient-centered communication with African American patients than with White patients (Johnson, Roter, Powe, & Cooper, 2004).…”
Section: Introductionmentioning
confidence: 99%